ROS-implicated apoptosis in Candida albicans: mechanistic insights into Aureobasidin A's antifungal activity - Yi, Jiaxin; Zhang, Qinghua; Zhou, Hao; Fei, Wei; Liao, Juan; Huang, Yi; Guo, Jun (Frontiers in Microbiology, 2026)
ObjectivesAureobasidin A (AbA) is a natural antifungal lipopeptide known to inhibit inositol phosphorylceramide (IPC) synthase. While its antifungal effect, mechanism via the inositol pathway involved in sphingolipid synthesis, and influence on ABC efflux pumps have been reported previously, its potential role in inducing programmed cell death and efficacy against oral candidiasis remain unexplored. This study aimed to elucidate a novel, complementary mechanism of AbA against Candida albicans (C. albicans), focusing on ROS-implicated apoptosis, and to evaluate its therapeutic potential for oral candidiasis.MethodsIn vitro experiments were initially conducted to assess the inhibitory effects of AbA on the virulence factors of C. albicans and investigate its impact on intracellular reactive oxygen species (ROS) levels and mitochondrial function to infer its potential apoptotic pathways. Subsequent transcriptome sequencing (RNA-seq) was employed to explore apoptotic mechanisms, with key genes validated by qRT-PCR. Finally, a murine oral candidiasis model was established to evaluate its in vivo antimicrobial activity and explore its clinical translational potential.ResultsAbA potently inhibited the growth and key virulence of C. albicans. Against strain SC5314, its minimum inhibitory concentration (MIC) was 0.0625 μg/mL, with 75% fewer colonies at 72 h. After 4 h treatment, intracellular reactive oxygen species (ROS) increased by 2.75-fold, and propidium iodide (PI) fluorescence confirmed apoptosis induction. RNA-sequencing (RNA-seq) showed activation of oxidative stress-related pathways, validated by qRT-PCR: oxidative stress genes (TSA1, NADPH oxidase, MCA1, CAT1) were significantly downregulated. These findings suggest that AbA induces apoptosis, a process critically mediated by the activation of the oxidative stress pathway. In murine models, 1-week topical AbA reduced tongue fungal burden by 80%, inflammatory cell infiltration area by 60%, and alleviated tongue pathological damage.ConclusionBeyond its known effect on sphingolipid synthesis, AbA exerts potent antifungal effects, which our data suggest involve the induction of ROS accumulation and subsequent mitochondrial dysfunction, leading to apoptosis. This dual mechanism highlights its promise as a therapeutic candidate, especially against azole-resistant infections.